2019
DOI: 10.4236/tel.2019.96127
|View full text |Cite
|
Sign up to set email alerts
|

IPO Underpricing and Predictive Power of Board Related Corporate Governance Mechanisms: A Study of Indian IPO Market

Abstract: Role of corporate governance indicators in IPO (Initial Public Offering) pricing is moderately researched area, however, a majority of these researches are found to be in context of other than Asian economies. Particularly, in context of Indian IPO market, only a few studies have been conducted in the past. Hence, the present study aspires to bridge this gap by examining the statistical significance of board-related corporate governance mechanisms in predicting the likelihood of IPO underpricing. This study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a longitudinal study on Indian IPOs, Singh et al (2020) found that from 1991 onwards, the amount of IPO capital grew at a rate of 11.54% compounded annually, while the number of IPO issues declined at a rate of 9.91% compounded annually. The average size of IPOs has increased by 21.46% annually (Jain et al , 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
“…In a longitudinal study on Indian IPOs, Singh et al (2020) found that from 1991 onwards, the amount of IPO capital grew at a rate of 11.54% compounded annually, while the number of IPO issues declined at a rate of 9.91% compounded annually. The average size of IPOs has increased by 21.46% annually (Jain et al , 2020).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Corporation governance is a key part of agency theory since the presence of non-executive directors ensures that management activities are supervised and demonstrates the preservation of shareholders' interests. According to agency theory, the agent-principal link may provide a moral problem that might lead to agency costs (Jensen and Meckling, 1976;Singh et al, 2019).…”
Section: Agency Theorymentioning
confidence: 99%
“…Traders and investors estimate an asset's volatility to examine past price swings and forecast future price changes. To determine the level of risk associated with an investment, one must examine the level of volatility (Singh et al, 2019(Singh et al, , 2022. It has been observed that high volatility is associated with high risk, so investors want to invest in the stocks with the least volatility.…”
Section: Introductionmentioning
confidence: 99%